Impact of Mitochondrial Permeability on Endothelial Cell Immunogenicity in Transplantation - Tran, Danh T. (Transplantation, 2018)
BACKGROUND: Microvascular endothelial cells (ECs) are central to an allograft’s immunogenicity. Cold ischemia and reperfusion injury associated with static cold storage and warm reperfusion activates ECs and increases the immunogenicity of the allograft. Following reperfusion, mitochondrial permeability transition pore (mPTP) opening contributes to mitochondrial dysfunction in the allograft, which correlates to alloimmune rejection. Current understanding of this relationship, however, centers on the whole allograft instead of ECs. This study aimed to elucidate the relationship between EC mPTP opening and their immuno-phenotype. METHODS: Mitochondrial metabolic fitness and glycolysis in ECs were assessed in parallel with metabolic gene microarray postreperfusion. NIM811 was used to inhibit mPTP opening to rescue mitochondrial fitness. The immunogenicity of NIM811-treated ECs was determined via levels of EC’s pro-inflammatory cytokines and allogeneic CD8(+) T cell co-cultures. Finally, EC surface expression of adhesion, co-stimulatory, co-inhibitory, MHC-I molecules, and MHC-I machinery protein levels were characterized. RESULTS: Genes for glycolysis, tricarboxylic acid cycle, fatty acid synthesis, gluconeogenesis were upregulated at 6 hours postreperfusion but either normalized or downregulated at 24 hours postreperfusion. As mitochondrial fitness was reduced, glycolysis increased during the first 6 hours postreperfusion. EC treatment with NIM811 during the early postreperfusion period rescued mitochondrial fitness and reduced EC immunogenicity by decreasing CCL2, KC release, and VCAM-1, MHC-I, TAP1 expression. CONCLUSIONS: Static cold storage and warm reperfusion leads to a reduction in mitochondrial fitness in microvascular ECs due to mPTP opening. Further, mPTP opening promotes increased EC immunogenicity that can be prevented by NIM811 treatment.